2020
DOI: 10.3389/fpsyt.2020.00341
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress Among Suicide Survivors: The Moderating Role of Self-Forgiveness

Abstract: Grief after suicide entails unique challenges and difficulties, such as intense feelings of anger and guilt, as well as various psychological risks. The current study examined the contribution of self-forgiveness (SF) to emotional distress (e.g., depressed mood and suicidal ideation) among suicide-loss survivors, compared with bereavement following sudden and expected death types. Bereaved individuals (N = 309; aged 18-84) completed questionnaires measuring SF, depressed mood, suicidal ideation, demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Oexle et al (2020) found that the perceived stigma of suicide comprised a significant factor leading to grief difficulties and suicide ideation. Levi-Belz and Gilo (2020), for example, found that self-forgiveness can act as a moderator that lessens intense depression and suicide ideation among individuals bereaved by suicide compared with individuals bereaved by other, nonsuicide deaths. Scharer and Hibberd (2019) found that perception of meaning in life may be associated with levels of depression among individuals bereaved by suicide, so that individuals having high levels of meaning in life were less likely to have from depression than those having low levels of meaning.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Oexle et al (2020) found that the perceived stigma of suicide comprised a significant factor leading to grief difficulties and suicide ideation. Levi-Belz and Gilo (2020), for example, found that self-forgiveness can act as a moderator that lessens intense depression and suicide ideation among individuals bereaved by suicide compared with individuals bereaved by other, nonsuicide deaths. Scharer and Hibberd (2019) found that perception of meaning in life may be associated with levels of depression among individuals bereaved by suicide, so that individuals having high levels of meaning in life were less likely to have from depression than those having low levels of meaning.…”
Section: The Present Studymentioning
confidence: 99%
“…It has been well-established, from both research and clinical practice, that individuals bereaved by suicide may experience prolonged feelings of guilt, self-blame, shame, anger, and self-doubt about what they could or should have done prior to the death to prevent it (Cerel et al, 2008; Feigelman & Cerel, 2020; Jordan, 2001). These emotions make them more prone to psychopathologies, such as complicated grief (Levi-Belz & Lev-Ari, 2019a), depression, and suicidal ideation and attempts (Jordan & McIntosh, 2011; Levi-Belz & Gilo, 2020; Young et al, 2012). Notably, however, only few studies have addressed the characteristics that may moderate the negative effect of a significant other's suicide on the bereaved individual's distress and mental health problems (e.g., Lev-Ari & Levi-Belz, 2019; Levi-Belz & Gilo, 2020; Levi-Belz & Lev-Ari, 2019a; Scharer & Hibberd, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…To date, the research literature on suicide bereavement has typically focused on the psychopathology associated with the loss, for example, in the context of U.S. or Australian samples (Kõlves & De Leo, 2018; Maple et al, 2018). Suicide-loss survivors have been shown to experience higher levels of depression, anxiety, and suicidal ideation and attempts (Cerel et al, 2017; Levi-Belz & Gilo, 2020; Maple et al, 2018; Pitman et al, 2014) relative to the nonexposed population. Evidence has also suggested that suicide-loss survivors may be at higher risk than individuals bereaved by the nonsuicide sudden death of a close person for a variety of psychological problems, including complicated grief and suicidal behavior (Andriessen, Krysinska, et al, 2017; Pitman et al, 2014).…”
mentioning
confidence: 99%
“…It also has the potential to combat stigma and contribute to reconciliation in relationships, including with the deceased, restored identities and even post-traumatic growth ( 36 , 37 ). The above meaning reconstruction has health benefits too, since feelings of blameworthiness have been associated with grief difficulties, complicated grief, PTSD, depression and other mental health difficulties ( 38 ), while the role of self-forgiveness in suicide bereavement has been linked to a decrease in depression and suicidality among suicide loss survivors ( 39 ). In addition, the results show that even very young children, can benefit from being included in family communication on and meaning reconstruction of the parent's suicide ( 40 ).…”
Section: Discussionmentioning
confidence: 99%